PENGARUH VARIASI TEKANAN DAN PENAMBAHAN UNSUR MAGNESIUM TERHADAP PENGECORAN ALUMINIUM PADA KOPLING PERAHU MOTOR - Harahap, Muhammad Rizki; Rizky Brillian Yuliandi; Taufikurahman; Ella Sundari; Dodi Tafrant (MACHINERY Jurnal Teknologi Terapan, 2024)
The universal joint coupling or U-joint is the part of the motor boat that connects the engine to the propeller shaft. The U-joint of a motor boat made of aluminum often suffers damage such as breaking due to loads when operating. The purpose of this research is to improve the quality of this product with the squeeze casting method with the addition of magnesium 3% and 4% and pressure variations of 70, 85 and 100 MPa for casting universal joint coupling products. The casting process is carried out by melting aluminum and mixing it with magnesium and then pressing it using a hydraulic pressure tool. After the casting process is complete, the specimen is trimmed for hardness testing. The results of the hardness test obtained the highest value on the pressure parameter of 100 MPa. For 4% Al-Mg with an emphasis of 100 MPa, the average hardness value was 94.66 BHN. For Al-Mg 3% with an emphasis of 100 MPa, the average value was 90.06 BHN. While the raw material has a hardness value of 57.52. It can be seen that the hardness value has increased from before. It can be concluded that the squeeze casting casting method and the addition of magnesium can affect the hardness value of aluminum.